Both harmful and (some) helpful behaviours from others are associated with increased expression of schizotypal traits. (30th May 2016) - Badcock, Johanna C.; Panton, Kirsten; Cohen, Alex; Badcock, David R.
Abstract: Negative treatment from others is related to elevated levels of trait schizotypy, signifying increased risk for psychosis, but associations with helpful behaviour have been much less studied. Using the Stereotype Content Model we tested the hypothesis that passive and active forms of help would be associated with increased and decreased expression of schizotypy, respectively. Schizotypal traits were assessed in students (N=631) using positive (Perceptual Aberration) and negative (Social Anhedonia) subscales of the Wisconsin Schizotypy Scales-Brief. Experiences of active (intentional) and passive (less deliberative) harm and help were assessed with the Behaviour from Intergroup Affect and Stereotypes Treatment Scale. As predicted, the results showed that experiences of passive help from others were associated with a 2–3 fold increase in scores on schizotypy scales, whilst reports of active help tended to be associated with a decrease in scores on these scales. Results also showed that increased reports of active and passive harm were associated with elevated scores on negative and positive schizotypy subscales, consistent with prior research. These findings, bridging research on social stereotyping and schizotypal personality, challenge the assumption that helpful behaviour from others is always beneficial for individuals with schizotypal traits who are at increased risk for psychosis. Highlights: We examined everyday experiences of harmful and helpful behaviour from others in relation to schizotypal traits. Counter to intuition, increased experience of passive help was associated with higher schizotypy scores. Higher social anhedonia scores were significantly associated with lower levels of active help. Increased reports of active and passive harm were associated with elevated levels of positive and negative schizotypal traits.